2012
DOI: 10.1002/maco.201206731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe and partial pressure of oxygen on the formation and phase transformation behavior of Al2O3 scale

Abstract: The effect of oxygen partial pressure on the phase transformation of Al2O3 scale on various Fe–Al alloys with and without very thin (∼100 nm) Fe coating was investigated. Fe‐coating on Fe–Al alloys can effectively suppress metastable Al2O3 formation, but little effect was observed when the samples were oxidized in a low partial pressure of oxygen. Under the low ${\rm P}_{{\rm O}_{{\rm 2}} } $ atmosphere, metastable to stable α‐Al2O3 scale phase transformation on both Fe‐coated and non‐coated Fe–Al alloys was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Intermediate is the transformation from the mentioned initial transient oxide to the one that satises said local equilibrium conditions. 7,[14][15][16][17][18][19][20][21][22] The properties of the transient oxide are indeed crucial for the alumina forming process, partial control of which may be gained by the so-called 3rd element effect. As rst observed in the Cu-Zn-Al system, 23 the 3rd element effect is understood to initiate and maintain formation of a protective a-Al 2 O 3 scale.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate is the transformation from the mentioned initial transient oxide to the one that satises said local equilibrium conditions. 7,[14][15][16][17][18][19][20][21][22] The properties of the transient oxide are indeed crucial for the alumina forming process, partial control of which may be gained by the so-called 3rd element effect. As rst observed in the Cu-Zn-Al system, 23 the 3rd element effect is understood to initiate and maintain formation of a protective a-Al 2 O 3 scale.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ high-temperature X-ray diffraction measurement clearly showed that the a-Al 2 O 3 , formed initially on alloys with higher Al content, had larger d-spacing and FWHM, because the a-Al 2 O 3 contained higher Fe and/or Cr contents. This Al 2 O 3 , which has larger d-spacing, was reported on Fe-high Al binary alloys [10,11]. Cr 2 O 3 and Al 2 O 3 form a solid-solution [12], but solubility of Fe 2 O 3 in Al 2 O 3 is relatively small, 5.3 mol% at 1000°C [13], thus the d-spacing of initially formed a-Al 2 O 3 on higher Cr alloys could be larger than that formed on a lower Cr alloy.…”
Section: Discussionmentioning
confidence: 77%
“…Initial formation of Fe 2 O 3 , which is isomorphous structure with a-Al 2 O 3 , promoted the transformation, but NiO formation retarded the transformation, which is likely due to the stabilization of metastable Al 2 O 3 [14]. We also found that the transformation to a-Al 2 O 3 was promoted on binary Fe-Al alloys with higher Fe content [17]. P. Brito et al also found same beneficial effect of Fe on promoting a-Al 2 O 3 scale formation on the binary Fe-Al alloys at lower temperature, 700°C [18].…”
Section: Introductionmentioning
confidence: 69%
“…In our previous study, we used binary Fe-Al alloys with different Al contents [17] (i.e., different Fe contents), and we found initial Fe 2 O 3 formation prior to development of an a-Al 2 O 3 scale on the alloys with lower Al (higher Fe). The peak positions of the initially formed Fe 2 O 3 moved toward higher-2h angle during heating.…”
Section: Suppression Of Metastable Al 2 O 3 Formationmentioning
confidence: 99%